2001
DOI: 10.3758/bf03196179
|View full text |Cite
|
Sign up to set email alerts
|

Impetus beliefs as default heuristics: Dissociation between explicit and implicit knowledge about motion

Abstract: We examined the extent to which findings from the literature on naive physics and representational momentum studies are consistent with impetus beliefs postulating imparted internal energy as a source of motion. In a literature review, we showed that, for situations in which impetus theory and physical principles make different predictions, representationalmomentum effects are consistent with impetus beliefs. In three new experiments, we examined people's implicit and explicit knowledge of the effect of mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
2
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 55 publications
(96 reference statements)
8
135
2
7
Order By: Relevance
“…This contrasts with the theory of Kozhevnikov and Hegarty (2001) who suggest that Bimplicitk nowledge of physics is erroneous but could be corrected by explicit knowledge, and the theory of Zago and Lacquaniti (2005), who propose that that perceptual physics knowledge is biased but our motor predictions use calibrated physics. The theories suggesting biased Bimplicit^physics have been based on evidence from the Brepresentational momentum^lit-erature that memory for the location of objects is shifted based on the dynamics of impetus physics rather than Newtonian mechanics (e.g., if two objects are moving downward on the screen then disappear, people will remember the larger object as having Bfallen^further than the smaller object; Hubbard 1997).…”
Section: The Accuracy Of the Intuitive Physics Enginecontrasting
confidence: 45%
See 3 more Smart Citations
“…This contrasts with the theory of Kozhevnikov and Hegarty (2001) who suggest that Bimplicitk nowledge of physics is erroneous but could be corrected by explicit knowledge, and the theory of Zago and Lacquaniti (2005), who propose that that perceptual physics knowledge is biased but our motor predictions use calibrated physics. The theories suggesting biased Bimplicit^physics have been based on evidence from the Brepresentational momentum^lit-erature that memory for the location of objects is shifted based on the dynamics of impetus physics rather than Newtonian mechanics (e.g., if two objects are moving downward on the screen then disappear, people will remember the larger object as having Bfallen^further than the smaller object; Hubbard 1997).…”
Section: The Accuracy Of the Intuitive Physics Enginecontrasting
confidence: 45%
“…However, our findings are not captured by this framework either. First, Kozhevnikov and Hegarty (2001) find that implicit knowledge is erroneous and explicit knowledge can correct these misconceptions, whereas we find more accurate physical principles from the system that would map onto the Bintuitive^beliefs. Second, both the catching and releasing trials were not immediate-they took a few seconds to resolve each-and yet we found no evidence that any of our participants were systematically using the same information they used on the drawing task.…”
Section: Prior Accounts Of Simulation Versus Logicmentioning
confidence: 67%
See 2 more Smart Citations
“…For example, people frequently prefer one explanation to another without explicitly being able to say why. They often seem to draw on implicit explanatory understandings that are not easy to put in explicit terms (Kozhevnikov & Hegarty 2001). Even without strictly adhering to the deductivenomological model of explanations, some explanations in domains such as biology hardly invoke laws at all (Bechtel & Abrahamsen 2005).…”
Section: What Explanations and Explanatory Understandings Arementioning
confidence: 99%